2019
DOI: 10.1021/acsami.9b04735
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Membrane-Camouflaged Black Phosphorus Quantum Dots Enhance Anticancer Effect Mediated by Apoptosis and Autophagy

Abstract: Hederagenin (HED) has poor anticancer activity whose mechanism remains unclear and unsystematic. Free drugs for cancer treatment exhibit disadvantages such as poor targeting and efficacy. To address this problem, we constructed a nanoplatform of black phosphorus quantum dots (BPQDs) camouflaged with a platelet membrane (PLTm) carrying HED, termed PLT@BPQDs-HED. PLTm vesicles serve as a shell to encapsulate multiple high-efficiency drug-loaded nanocores, which can target tumor sites and significantly improve an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 51 publications
1
67
0
Order By: Relevance
“…Due to such targeting effect, PM/PLGA/DTX showed higher inhibition of tumor growth in vivo. Moreover, PNPs have been made with different cores to deliver various anticancer compounds for the treatment of cancers in mouse xenograft models of colorectal cancer (HT29 cells), [63] liver cancer (H22 cells), [64] breast cancer (MCF-7 cells), [65] and ovarian cancer (SK-OV-3 cells). [66] In addition to small-molecule anticancer compounds, PNPs were also used to target small interfering RNA (siRNA) in vivo to silence tumor-relevant genes (Figure 4).…”
Section: Targeting Cancer Cells For Cancer Treatment and Detectionmentioning
confidence: 99%
“…Due to such targeting effect, PM/PLGA/DTX showed higher inhibition of tumor growth in vivo. Moreover, PNPs have been made with different cores to deliver various anticancer compounds for the treatment of cancers in mouse xenograft models of colorectal cancer (HT29 cells), [63] liver cancer (H22 cells), [64] breast cancer (MCF-7 cells), [65] and ovarian cancer (SK-OV-3 cells). [66] In addition to small-molecule anticancer compounds, PNPs were also used to target small interfering RNA (siRNA) in vivo to silence tumor-relevant genes (Figure 4).…”
Section: Targeting Cancer Cells For Cancer Treatment and Detectionmentioning
confidence: 99%
“…Platelets have pathophysiological affnity with tumors [20]. The interaction between P-selectin and CD44 partially contributes to the binding of PM-camouflaged nanomaterials to the surface of breast cancer cells [4,21].…”
Section: Effect Of Irradiation On the Endocytosis Of Pinps@pm By Cancmentioning
confidence: 99%
“…Platelets have pathophysiological affnity with tumors [20]. The interaction between P-selectin and CD44 partially contributes to the binding of PM-camou aged nanomaterials to the surface of breast cancer cells [4,21]. After aggregation on the cell membrane, our data showed that PINPs@PM was endocytosed by 4T1 cells in a time-dependent manner.…”
Section: Effect Of Irradiation On the Endocytosis Of Pinps@pm By Cancmentioning
confidence: 76%